LATENT PREDICTORS OF SEVERE PREECLAMPSIA AS A FORM OF SECONDARY THROMBOTIC MICROANGIOPATHY IN PREGNANT WOMEN (World Bulletin of Social Sciences, 2025)
To analyze the clinical-demographic characteristics, latent risk factors, and functional (laboratory and instrumental) predictors of severe preeclampsia (sPE) as a form of secondary thrombotic microangiopathy (TMA).